Metabolic Symbiosis and Immunomodulation: How Tumor Cell-Derived Lactate May Disturb Innate and Adaptive Immune Responses - Morrot, Alexandre; Fonseca, Leonardo Marques da; Salustiano, Eduardo J.; Gentile, Luciana Boffoni; Conde, Luciana; Filardy, Alessandra Almeida; Franklim, Tatiany Nunes; da Costa, Kelli Monteiro; Freire-de-Lima, Celio Geraldo; Freire-de-Lima, Leonardo (Frontiers in Oncology, 2018)
The tumor microenvironment (TME) is composed by cellular as well as non-cellular components. Examples include: (i) bone marrow-derived inflammatory cells, (ii) fibroblasts, (iii) blood vessels, (iv) immune cells and (v) extracellular matrix (ECM) components. In most cases, this combination of components may result in an inhospitable environment, in which a significant retrenchment in nutrients and oxygen considerably disturbs cell metabolism. Cancer cells are characterized by an enhanced uptake and utilization of glucose (Glc), a phenomenon described by Otto Warburg over 90 years ago. One of the main products of this reprogrammed cell metabolism is lactate. “Lactagenic” or lactate-producing cancer cells are characterized by their immunomodulatory properties, since lactate, the end product of the aerobic glycolysis, besides acting as an inducer of cellular signaling phenomena to influence cellular fate, might also play a role as an immunosuppressive metabolite. Over the last ten years, it has been well accepted that in the TME, the lactate secreted by transformed cells is able to compromise the function and/or assembly of an effective immune response against tumors. Herein, we will discuss recent advances regarding the deleterious effect of high concentrations of lactate on the tumor-infiltrating immune cells, which might characterize an innovative way of understanding the tumor-immune privilege.